Outcomes in patients with pulmonary hypertension undergoing percutaneous atrial septal defect closure. Issue 9 (11th October 2007) - Balint, O H; Samman, A; Haberer, K; Tobe, L; McLaughlin, P; Siu, S C; Horlick, E; Granton, J; Silversides, C K
Abstract : Objectives: To examine the outcomes in patients with moderate or severe pulmonary arterial hypertension (PAH) undergoing percutaneous atrial septal defect (ASD) closure. Design: Retrospective study. Setting: Teaching hospital-based study. Patients: Fifty-four patients with moderate (n = 34) or severe PAH (n = 20) who underwent successful device implantation between 1999 and 2004 were included in the study. Clinical and transthoracic echocardiographic data were reviewed. Pulmonary hypertension was classified as moderate (50–59 mm Hg) or severe (⩾60 mm Hg) according with the right ventricular systolic pressure (RVSP) calculated by echocardiography. Results: At the early follow-up (mean (SD) 2.3 (1.2) months) all patients were alive and the baseline RVSP decreased from 57 (11) mm Hg to 51 (17) mm Hg (p = 0.003). At the late follow-up (n = 39, mean (SD) duration 31 (15) months) two patients had died and the baseline RVSP decreased from 58 (10) mm Hg to 44 (16) mm Hg (p = 0.004). Although the overall mean RVSP decreased at late follow-up, only 43.6% (17/39) of patients had normalisation (<40 mm Hg) of the RVSP and 15.4% (6/39) had persistent severe PAH. Conclusion: Transcatheter closure in patients with secundum ASD and PAH can be successfully performed in selected subjects and is associated with good outcomes. Early improvements in RVSP are seen in patients with moderate or severe PAH undergoing transcatheter ASD closure. Continued improvement in RVSP occurs in late follow-up. Despite decreases in the mean RVSP in late follow-up, many patients do not have complete normalisation of pressures.